Job Safety Analysis of Repair Multi-Media Filter (Confined Space) in Agribusiness and Industry Sector - Hosiah Sahur; Denny Ardyanto; Moch. Sahri; Muhammad Iqbal Ridho Maulana Arifin (Poltekkes Kemenkes Surabaya, 2025)
Working in confined spaces is inherently more dangerous than in other environments due to the various unexpected components and factors that must be assessed when identifying hazards. Job Safety Analysis (JSA) effectively identifies risks in non-routine operations and prevents accidents. This study aims to analyze and minimize the risks associated with repair work on the Multi-Media Filter (MMF) confined space tank in the Agribusiness and Industry Sector. The method employed is a descriptive observational Job Safety Analysis, with data collected on work stages, potential hazards, control methods, and hazard ratings for each job. The MMF tank repair work in confined spaces involves eight activities, with 27 identified hazards and risks. Of these, two jobs (15%) fall into the low-risk category, while six jobs (85%) are classified as medium risk; no high-risk jobs were found. The MMF tank repair work presents medium and low risks for each job. Workers can safely carry out the repair work, as no high-potential hazards were identified, ensuring their safety. It is recommended that the JSA be periodically updated, involving workers in the evaluation process to ensure continuity and relevance.